Francisco Ferrer, une figure inspirante pour les mouvements de rénovation pédagogique de la transition démocratique espagnole ? (1975-1978) - Cécile Morzadec (Éducation et Socialisation)
This article sets out to examine the place of the figure of Francisco Ferrer y Guardia, and his model of the Modern School, in Spain's collective memory at the time of Franco's death in 1975, by combining textual analysis and unpublished oral interviews. After briefly outlining the programme of the Modern School to determine the extent to which it constituted an example of socialising education, we will use four educational journals and five prefaces published between 1975 and 1978 to examine the resurgence of the figure of Ferrer and the way in which it is revisited in the light of a new historical, political and educational context. Testimonies gathered between 2021 and 2022 from those involved in Spanish educational renewal will enable us to complete our observations by asking questions about Ferrer's place in teacher training, the relevance of his pedagogical proposals to teaching practices, and the different ways in which his work can be accessed after years of invisibility during the Franco era.